Vožnja pod vplivom alkohola in prometna varnost - Rus-Makovec, Maja (Zdravniški vestnik, 2010)
Background: The mobility facilitated by road transport enables many people to enjoy a lifestyle characterized by flexibility and independence. However, it comes at a price of many deaths and injuries. Alcohol is by far the most prevalent psychoactive substance that affects drivers. Basic ideas about neurobiology of alcohol dependency are presented to underline the pathologicalnature of dependency and to differentiate between non-dependent and alcohol dependent drivers. Offenders - drinking drivers can be sentenced to mandatory participation in some form of short psychotherapeutic intervention. Screening and assessment are needed to refer the offender to themost appropriate intervention and/or treatment according to their dependency or non-dependency status. Conclusion: Combining short psychotherapeutic interventions (treatment) outside medical system with non-treatment sanctions that prevent offenders from drinking and driving (license revocation, alcohol ignition interlocks) reduces the publicćs risk while non-dependent offenders are given support for a more stable change of behavior. The best treatment strategies include motivation enhancement and a combination of group cognitive-behavioral techniques with some education. Alcohol dependent drivers cannot benefit from short psychotherapeutic intervention programs for non-dependent offenders because of pathologically changed neurobiology and should be referred to alcohol addiction treatment in designated healthcare institutions.
Keywords: Accidents, Traffic; Alcohol Drinking; Alcoholism; alkohol; Alkohol, pitje; alkoholiki; Alkoholizem; Automobile Driver Examination; Diagnosis; Legislation And Jurisprudence; Nesreče prometne; pitje; prometna varnost; Therapy; ukrepi; vozniki; Vozniki avtomobila, preiskava; zdravljenje